Cash holdings, leverage, ownership concentration and board independence: evidence from Malaysia / Rahayu Izwani Borhanuddin and Pok Wee Ching. - Borhanuddin, Rahayu Izwani; Pok, Wee Ching (Universiti Teknologi MARA Cawangan Selangor, 2011)
The study aimed to investigate the relationship between cash holdings and leverage of Malaysian companies. The present study also attempted to compare the relationship of cash holdings and leverage between sample of firms having low level of ownership concentration and high level of board independence (good corporate governance) and sample of firms that having high level of ownership concentration and low level of board independence (poor corporate governance). Leverage, cash flow variability, liquidity, growth, size and capital expenditure were used as corporate cash holdings determinants. The final sample of the study consisted of 276 companies with 875 observations from six main industries on the Main Board of Bursa Malaysia over a period of four years (2002 to 2005). Linear regression analysis was used to examine the relationship between cash holdings and leverage. The results show that there were significant negative relationships between cash holdings and leverage with or without control variables. The results also show that companies that had poor corporate governance held a higher level of cash compared to companies that practised good corporate governance.